When does Reckless Driving Occurs? Case Study in Nampula, Mozambique - Fernando, Celso L.; Mucufo, Jaibo (Technium Social Sciences Journal, 2024)
This study investigates the influence of traffic conditions on reckless driving behavior in Nampula, Mozambique, where road accidents claim several lives daily. Previous research has largely focused on individual driving behaviors, neglecting the impact of traffic environments on such behaviors. This study addresses this gap by categorizing vehicles into four groups: passenger cars, minibuses, trucks, and motorcycles, and classifying traffic conditions using k-means clustering. Three distinct traffic patterns were identified: Motorcycle and Car Dominant Traffic (MCDT), High-Density Traffic Flow (HDTf), and Low-Density Traffic Flow (LDTf). Results show that reckless driving is significantly influenced by traffic conditions, with minibuses, motorcycles, and trucks being key contributors. Pattern 2 (HDTf) demonstrated the highest occurrence of reckless driving, driven by competition among minibus drivers, the obstructive presence of trucks, and risky motorcycle maneuvers. Pattern 1 also exhibited elevated risk, particularly performed among motorcycle riders, while Pattern 3 (LDTf) showed the lowest risk due to reduced traffic density. Poisson regression analysis revealed that increased traffic flow in any vehicle category is associated with higher rates of reckless driving. Minibuses and motorcycles, functioning as demand-oriented public transport, engage in competitive and unsafe behaviors, while trucks, though not engaging in reckless driving directly, act as barriers that exacerbate risky maneuvers by other vehicles. These findings highlight the need for dedicated lanes for minibuses and motorcycles and tailored traffic safety policies to mitigate reckless driving.